Earning your stripes: a second species of striped gecko in the New Zealand gecko genus Toropuku (Gekkota: Diplodactylidae) - Hitchmough, Rodney A.; Nielsen, Stuart V.; Bauer, Aaron M. (Zootaxa, 2020)
The New Zealand diplodactylid gecko genus Toropuku is currently monotypic, but the sole member of the genus, T. stephensi, is distributed in two disjunct, geographically distant regions of New Zealand – the islands of Cook Strait (which includes the type locality, Stephens Island), between New Zealand’s North and South Islands, and the Coromandel Peninsula, in the northeastern North Island. Previously published phylogenetic results, based on three total individuals, recognized substantial—possibly species-level—diversity between these disparate localities, although no taxonomic decisions were made at that time. More recently, additional animals have been found on the Coromandel Peninsula. We here present phylogenetic and morphological evidence based on this expanded dataset to formally describe the populations on the Coromandel Peninsula as a new species, Toropuku inexpectatus sp. nov. The specific epithet refers to the species’ surprise discovery in a herpetologically well-surveyed area. The recognition of T. inexpectatus sp. nov. as a distinct species has implications for the conservation status of T. stephensi, which is now considered restricted to three islands in Cook Strait.